Intergranular corrosion at a modified surface layer in a supermartensitic stainless steel for chemical injection mandrel. (July 2021) - Tavares, S.S.M.; Keide, H.L.A.; Garcia, P.S.P.; Velasco, J.A.C.; Pardal, J.M.; Baptista, I.P.
Highlights: Pipes of supermartensitic stainless steel were uncorrectly submited to carburization. An austenitic and sensitized layer was formed, with lower corrosion resistance. Intergranular attack was observed in four bend tests with H2 S partial pressure 0.2 psia. SCC cracks were observed in four bend tests with H2 S partial pressure 1.0 psia. Abstract: Supermartensitic stainless steels (SMSSs) are commonly employed as pipes and mandrels in off-shore oil and gas production. These materials are known to exhibit higher corrosion resistance than conventional martensitic stainless steels and also present a lower installation cost than duplex/superduplex steels and Ni alloys. After the occurrence of a certain number of failures of mandrels, manufacturers purchased samples of pipes and forged fittings in order to promote several stress corrosion tests. In this work, the specimens obtained from a grade UNS S41426 pipe steel failed at the four point test under milder conditions than the limit of NACE 0175/ISO 15156 standard. The metallurgical analysis revealed that the pipe purchased by a specific producer has been carburized at high temperature, probably as an attempt to improve superficial hardness and wear resistance. However, it resulted in an inadequate microstructure with sensitized austenitic grains, without significant increase of superficial hardness. Consequently, the material suffered severe corrosion attack during the four point tests, indicating high chances of failure at service conditions.